1999
DOI: 10.1016/s0741-5214(99)70389-7
|View full text |Cite
|
Sign up to set email alerts
|

p53 gene transfer to the injured rat carotid artery decreases neointimal formation

Abstract: Adenovirus-mediated gene transfer of p53 protein significantly decreases the formation of neointima in the rat carotid injury model. This may represent a potential therapy for restenosis in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 24 publications
3
19
0
1
Order By: Relevance
“…Adenoviruses were propagated in HEK 293 cells and purified by CsCl density gradient centrifugation. A recombinant adenovirus encoding for the wild-type p53 protein was a generous gift from Enrico Ascher (24,35).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenoviruses were propagated in HEK 293 cells and purified by CsCl density gradient centrifugation. A recombinant adenovirus encoding for the wild-type p53 protein was a generous gift from Enrico Ascher (24,35).…”
Section: Methodsmentioning
confidence: 99%
“…The importance of p53 is also confirmed in various animal models. Adenovirus-mediated gene transfer of p53 to rat carotid arteries inhibited neointimal formation following balloon injury (24), whereas target deletion of p53 led to larger intimal lesions in a mouse vein graft model (25).…”
Section: Apoptosis Of Vascular Smooth Muscle Cells (Smcs)mentioning
confidence: 99%
“…Brachytherapy, based on the principle that proliferating cells are more sensitive to ionizing radiation, has shown favorable results in initial clinical trials, 2 but long-term efficacy and safety remain a concern. 3 In contrast, molecular approaches with transfer of the cytotoxic thymidine kinase, 4 retinoblastoma, 5 nitric oxide synthase (NOS), 6 -9 and tumor suppressor 10,11 genes have shown benefit in reducing neointima formation in rodent and porcine balloon-injured peripheral arteries. Most gene-based strategies have been tested in the carotid artery balloon denudation model.…”
mentioning
confidence: 99%
“…23 In addition, it has been shown that wildtype p53 accumulates in human atherosclerotic tissues. 24 Moreover, adenovirus expression of p53 (Ad-p53) reduces cell proliferation in the rat carotid artery 25 or migration in the human saphenous vein 26 and conversely, antisense oligonucleotides to p53 increase proliferation. 27 All these studies suggest that p53 inhibits cell proliferation and promotes VSMC apoptosis in atherosclerosis, in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%